Absolute vs. relative success: Why overconfidence is an inefficient equilibrium - Alice Soldà; Changxia Ke; William von Hippel; Lionel Page (University of Heidelberg, Department of Economics, 2021)
Overconfidence is one of the most ubiquitous biases in the social sciences, but the evidence regarding its overall costs and benefits is mixed. To test the possibility that overconfidence might yield important relative benefits that offset its absolute costs, we conducted an experiment (N=298 university students) in which pairs of participants bargain over the unequal allocation of a prize that was earned via a joint effort. We manipulated confidence using a binary noisy signal to investigate the causal effect of negotiators' beliefs about their relative contribution on the outcome of the negotiation. Our results provide evidence that high levels of confidence lead to relative benefits (how much one earns compared to one's partner) but absolute costs (how much money one receives overall). These results suggest that overconfidence creates an inefficient equilibrium whereby overconfident negotiators benefit over their partners even as they bring about joint losses.
urn:nbn:de:bsz:16-heidok-295132
Keywords: 330; Overconfidence; motivated beliefs; negotiation